Variability and trends of the tropical tropopause derived from a 1980–2021 multi-reanalysis assessment - Zou, Ling; Hoffmann, Lars; Müller, Rolf; Spang, Reinhold (Frontiers in Earth Science, 2023)
As the tropopause plays a key role in regulating the entry of air from the troposphere into the stratosphere and in controlling stratosphere-troposphere exchange, variation of the tropopause impacts the atmospheric dynamics, circulation patterns, and the distribution of greenhouse gases in the upper troposphere and lower stratosphere (UTLS). Therefore, it is of particular interest to investigate the climatological characteristics and trends of the tropopause. Previous studies have investigated the tropopause characteristics using reanalyses and multi-source observations. This study extends the analysis of long-term variability and trends of tropical tropopause characteristics in earlier studies from 1980 up to 2021 using the modern ERA5 reanalysis and compares the results with those of other reanalyses, including ERA-Interim, MERRA-2, and NCEP1/2. Our analysis reveals a general rise and cooling of the tropical tropopause between 1980 and 2021. The geopotential height has increased by approximately 0.06±0.01 km/decade (at a 95 % confidence level), while the temperature has decreased by −0.09±0.03 K/decade (at a 95 % confidence level) for both the lapse rate tropopause (LRT) and the cold point tropopause (CPT) in ERA5. However, from 2006 to 2021, ERA5 shows a warming tropical tropopause (0.10±0.11 K/decade) along with a slower rise in tropopause height (0.05±0.02 km/decade) (at a 95 % confidence level). Furthermore, our analysis demonstrates a decline in the rise and cooling of the tropical tropopause since the late 1990s, based on moving 20-year window trends in ERA5. Similar trends are observed in other investigated reanalyses. In addition, this study evaluated the variability of the width of the tropical belt based on tropopause height data from the reanalyses. The ERA5 data show a narrowing tropical belt (−0.16±0.11 • /decade) for the time period 1980-2021 according to the relative threshold method. It reveals a tropical widening (0.05±0.22 • /decade) for the period between 1980 and 2005, followed by a tropical narrowing (−0.17±0.42 • /decade) after 2006. However, the large uncertainties pose a challenge in drawing definitive conclusions on the change of tropical belt width.